Morphometric Analyses of Aksu Stream And Batlama Creek Watersheds That Caused Flood and Overflows in Giresun - Avci, Vedat; Sunkar, Murat (Istanbul Univ, Fac Letters, Dept Geography, 2015)
In this study, the morphometric characteristics of Aksu stream and Batlama creek that caused flood and overflows in Giresun have been analyzed. The risk of flood of Giresun is high because it is located on Eastern Black Sea. Black Sea region is one of the areas where the most frequently floods are occurred in Turkey because of its geomorphologic features and climatic conditions. The important flood that causes the loss of life and property in Giresun stems from Aksu Stream in the east and Batlama Creek in the west of the city. The climate, lithologic and geomorphologic characteristics, vegetation and improper land use of these stream basins are effective in the occurrence of flood and overflows. In this study, the morphological features of these rivers within the geomorphologic characteristics that are effective in the formation of the flood have been analyzed. The change in climate and vegetation occurs rapidly in the flood, but the changes in the morphometry watershed occur in a long time. For this reason, morphometric analysis in the study of floods is important. Spatial and relief analysis have been conducted in order to determine the morphometric characteristics of watersheds of Aksu and Batlama. When the obtained findings and climate features of these rivers are evaluated it is high risk in terms of flood. For this reason, it is important to consider the morphometry of watershed in the studies about flood and overflows.
Keywords: Giresun; Aksu Stream; Batlama Creek; Flood and Overflows; Morfometric analyses